Transitioning toward net-zero residential buildings (N-ZRBs) on the Arabian Gulf Region - Alhawas, Mosad M. H. (2024)
This research investigates residential building energy performance and feasible energy efficient measures to achieve Net Zero Energy Homes (NZEHs) on the eastern Arabian Gulf peninsula, considering the local vernacular architecture context and passive cooling techniques, regional hot and humid climate conditions, occupants' needs, and cultural requirements. The simple definition of an (NZEH) is when the building is energy-self-sufficient throughout the year. This research investigation has been accomplished through a comprehensively staged research methodology. It included an extensive literature review examining how ancestral communities coped with the harsh climate of the east coast of the Arabian Gulf peninsula in the absence of electricity. Additionally, it involved an analysis of the energy consumption trends in residential buildings within the region, identifying key design characteristics typical to Arabian Gulf residential buildings, and using computer modeling IESVE to illustrate a future Net Zero Energy Home (NZEH) of the region.